Firm Size Moderates Transfer Pricing and Capital Intensity Effects on Tax Avoidance - Ningrum, Radhita Nur Arie Setya; Nadi, Luh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Tax avoidance practices remain a concern because they have the potential to reduce government revenue through the exploitation of loopholes in tax regulations. Furthermore, previous studies on the effects of transfer pricing, capital intensity, and firm size on tax avoidance still show inconsistencies. This study aims to analyze the effects of transfer pricing and capital intensity on tax avoidance, with firm size serving as a moderating variable. The study employs an associative quantitative method using secondary data in the form of annual financial reports from companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange for the period 2020–2025. The sample consists of 33 companies (198 observations) selected using purposive sampling. Data analysis was conducted using panel data regression with EViews 13 and Microsoft Excel. The results indicate that transfer pricing and capital intensity simultaneously influence tax avoidance. Partially, transfer pricing has no effect, whereas capital intensity does influence tax avoidance. Firm size also fails to moderate the effects of the two independent variables on tax avoidance. These findings are expected to enrich the tax literature and provide insights for companies and regulators in formulating tax policies.